Desenvolvimento de ligas de alumínio recicladas contendo a fase primária Al(Fe,TM)Si aproximante de quasicristal: controle da microestrutura visando aplicações tribológicas e mecânicas - Ferreira, Tales (Universidade Federal de São Carlos, 2021)
Iron is the most common and harmful impurity to the mechanical properties of casting Al-7Si-3Cu alloys, which are widely used in the automotive industry. Due to the economic and environmental advantages of recycling, there is great interest in controlling the microstructure of these alloys containing deleterious Fe-rich phases. In this context, the present work aims to study the mechanical properties of Al-7Si-3Cu-1Fe alloy by controlling the distribution and morphological characteristics of an α-Alx(Fe,TM)ySiz quasicrystal approximant phase. Two microstructures were produced from the recycled Al-7Si-3Cu-1Fe alloy. In the first, it was decided to control the microstructure in order to develop a material with high tribological properties. In the second, it sought to produce a microstructure that combined high resistance and ductility, even at room temperature. For the first microstructure, combined Mn and Cr additions and a new rotational outward solidification casting process were used to control the formation and distribution of the α-phase. For the second, a processing sequence using spray forming, hot rotary-swaging and Si globulization heat treatment, combined with Mn and V additions, were used to control the morphological aspects of this phase of interest. Tribological tests up to 300 ºC showed that the first microstructure ensured low coefficient of friction and wear resistance that exceed most of Al-alloys. The tensile properties of the second microstructure showed up to 250 ºC a superior combination of strength and ductility in comparison with Al-Si based alloys contaminated with high Fe contents (≥ 1.0 wt%). The results presented here showed that, by controlling the morphological and distribution of the α-phase, it is possible to tailor the microstructure of recycled Al-7Si-3Cu-1Fe alloy to achieve different optimized mechanical properties.
Development of recycled aluminum alloys containing the primary Al(Fe,TM)Si quasicrystal approximant phase: microstructure control aiming tribological and mechanical applications
Keywords: Reciclagem; Ligas de Al; Fase-α aproximante de quasicristal; Controle da microestrutura; Propriedades mecânicas em altas temperaturas; Recycling; Al-alloys; Quasicrystal approximant α-phase; Microstructure control; High temperature mechanical properties; CIENCIAS EXATAS E DA TERRA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO::FUNDICAO; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA::ESTRUTURA DOS METAIS E LIGAS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA::PROPRIEDADES FISICAS DOS METAIS E LIGAS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA::TRANSFORMACAO DE FASES